Role of Re-Resection in Non–Muscle-Invasive Bladder Cancer - Harry W. Herr (The Scientific World Journal)
Restaging, or second transurethral resection (TUR), is essential to successful management of high-risk, non–muscle-invasive bladder cancer. Here we review the relevant literature documenting the role of restaging TUR. Cohort and randomized studies show that restaging TUR detects more tumors than initial TUR, improves clinical staging, and reduces the frequency of early tumor recurrences. Our conclusions show thatrestaging TUR improves the outcomes of high-risk, non–muscle-invasive bladder neoplasms.